To study the prevalence of overweight and obesity and its associated risk factors in a youth population in an urban slum in a metropolitan city - Kamble, Shyamal S.; Hadaye, Rujuta S. (International Journal Of Community Medicine And Public Health, 2025)
Background: Obesity, the most prevalent form of malnutrition, affects children and adults alike. A risk factor for Diabetes Mellitus, Hypertension, Cancer, Cardiovascular diseases, and entity on its own, thereby increasing the morbidity and mortality of individual and community enmasse. Methods: The study was conducted in the community field practice area of Urban Health Centre of Topiwala National Medical College & B.Y.L Nair Hospital, Mumbai. 210 participants were selected for the study using simple random sampling method. One-to-one interviews were conducted using semi-structured interview schedule. Prevalence of overweight and obesity was calculated based on the obtained anthropometry information. Results: The study found the overall prevalence of overweight/ obesity to be 17.2% in 15 to 24 years’ age group. The prevalence of overweight was 14.3% and of obesity was 2.9% in the study population based on BMI. The study also found 13.3% adult study participants to have high Waist to Hip Ratio (WHR) which signified abdominal fat deposition. Interestingly, all the participants with high WHR were females. The study found significant association between sex of the participant and overweight and obesity. Conclusion: The study concluded that the prevalence of overweight was 14.3% and obesity was 2.9% in the youth population of an urban slum in a metropolitan city. The study found high WHR among 13.3% of adult study population. Among the sociodemographic risk factors, sex of the participant was found to be of significant association for predisposition of overweight / obesity in the current study.